Policies to combat organized crime in Europe: The Italian experience - Michele Mosca (The Journal of European Economic History, 2020)
Combating the expansion of criminal organizations has long been on the agenda of the European Union, but to date the steps towards the adoption of a common strategy have been timid. And this despite the European Union's request for alignment of the laws and regulations of the Member States. Intensive work commencing in 2012 eventually produced Directive 2014/42EU on the freezing and confiscation of instrumentalities and proceeds of crime in the European Union, modelled on Law 109/1996 enacted by Italy. Another step in this direction was the approval in 2016 by the European Parliament of the report on the fight against corruption, which renews the Commission's request for criminal association to be made punishable and for the adoption of specific legislation on "a particular type of criminal organization whose members take advantage of the power of intimidation of the associative bond and of the condition of subjection and silence" (Article 416-bis of the Italian penal code), allowing "confiscation in the absence of definitive conviction." Harmonized legislation has yet to be adopted, however; in particular, there is no reference model for combating criminal organizations in economic terms or for the construction of barriers in civil society. The Italian experience in the fight against mafia-style criminal organizations, based on the social reutilization of confiscated assets and the construction of an economy alternative to organized crime, could be a useful reference model for EU member countries in constructing a homogeneous European system for combating criminal gangs.
Keywords: 330